Comparison of the RGM medium and the mycobacterial growth indicator tube automated system for isolation of non-tuberculous mycobacteria from sputum samples of cystic fibrosis patients in Belgium. (December 2018) - Scohy, Anaïs; Gohy, Sophie; Mathys, Vanessa; Sapriel, Guillaume; Toussaint, Laëtitia; Bressant, Florian; Zitouni, Ali; Teylaert, Marie-Noël; Vander Meeren, Marie-Christine; Colmant, Alexandre; Simon, Anne; Perry, John D.; et al.
Abstract: Purpose: Pulmonary infections due to non-tuberculous mycobacteria (NTM) are an emerging issue in the cystic fibrosis (CF) population. Due to bacterial and fungal overgrowth, isolation of mycobacteria from the sputum samples of these patients remains challenging. RGM medium, a novel agar-based culture medium was evaluated for the isolation of NTM from sputum samples of CF patients. Methodology: Sputum samples were inoculated onto RGM medium and conventional Mycobacterial Growth Indicator Tube( MGIT™, Becton Dickinson, USA). Agar plates were incubated at 35 °C and growth was recorded once a week during 42 days. We compared the yield of the two media. Results: 217 samples were obtained from 124 CF patients. 20 samples (13 patients) had a positive culture for NTM. 79/217 (36.4%) MGIT had to be discontinued due to contamination compared to 18/217 (8.3%) for RGM. We reported equivalent NTM detection performances for RGM and MGIT ( P  = 0.579): these media enabled the isolation of 15 and 12 NTM strains respectively. Conclusion: RGM medium increases the proportion of interpretable results and the number of NTM cultured. Taking into account the non-inferiority compared to conventional methods and ease of use of RGM medium, we estimate that this test can replace current approaches for the screening of NTM among people with CF. Additionally, RGM provides semi-quantitative results (number of colonies) and information on the morphology of colonies, which may be clinically relevant information.